Comparison of Different Vitrification Procedures on Developmental Competence of Mouse Germinal Vesicle Oocytes in the Presence or Absence of Cumulus Cells - Saeed Zavareh (International Journal of Fertility and Sterility, 2009)
Background An evaluation of the developmental competence of vitrified mouse germinal vesicle (GV) oocytes with various equilibration and vitrification times; in the presence or absence of cumulus cells and by comparison between the cryotop method and straws was performed.